Lyme borreliosis and skin - Biju Vasudevan; Manas Chatterjee (Wolters Kluwer Medknow Publications, 2013)
Lyme disease is a multisystem illness which is caused by the strains of spirochete Borrelia burgdorferi sensu lato and transmitted by the tick, Ixodes. Though very commonly reported from the temperate regions of the world, the incidence has increased worldwide due to increasing travel and changing habitats of the vector. Few cases have been reported from the Indian subcontinent too. Skin manifestations are the earliest to occur, and diagnosing these lesions followed by appropriate treatment, can prevent complications of the disease, which are mainly neurological. The three main dermatological manifestations are erythema chronicum migrans, borrelial lymphocytoma and acrodermatitis chronica atrophicans. Many other dermatological conditions including morphea, lichen sclerosus and lately B cell lymphoma, have been attributed to the disease. Immunofluorescence and polymerase reaction tests have been developed to overcome the problems for diagnosis. Culture methods are also used for diagnosis. Treatment with Doxycycline is the mainstay of management, though prevention is of utmost importance. Vaccines against the condition are still not very successful. Hence, the importance of recognising the cutaneous manifestations early, to prevent systemic complications which can occur if left untreated, can be understood. This review highlights the cutaneous manifestations of Lyme borreliosis and its management.